WATER QUALITY OF POST CONTAMINATION OF MARINE DEBRIS IN THE KUTA BEACH OF BALI - Aprizon Putra; Semeidi Husrin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Kuta Beach of Bali is one of the top tourist destination for a vacation in Bali Island. The beauty of the beach with white sand, ocean waves are excellent for surfing, sunset, and tourism infrastructure which detailed makes very famous Kuta beach to foreign countries. However, in recent years the beauty of Kuta beach which has become an icon of tourism in Bali began plagued by high levels of contaminant of the marine debris on the beach, mainly contamination of the marine debris that often accumulate in Kuta beach every season West. The purpose of this study was to determine the condition of water quality based the quality standards of sea water KMNLH Number 51 Years 2004 post contamination of the marine debris that occurred in the Kuta beach of Bali. The method used is to perform measurements using a